2021
DOI: 10.3390/jcm10194298
|View full text |Cite
|
Sign up to set email alerts
|

What Is the Importance of Electrocardiography in the Routine Screening of Patients with Repaired Tetralogy of Fallot?

Abstract: Background: In patients following complete repair of the tetralogy of Fallot, the duration of the QRS complex is associated with the size and mechanical function of the right ventricle, which are contemporarily assessed by cardiac magnetic resonance (CMR). Methods: 38 patients aged 18.0–54.9 years (median age 24.9 years) who had undergone complete repair of the tetralogy of Fallot were examined using CMR and concomitant 24 h ambulatory electrocardiography monitoring. We used statistical analysis to investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Surgical implantation of PV in RVOT is a difficult procedure because the oversize prostheses will invariably get compressed anteriorly by the sternum or compromised at the bifurcation of the pulmonary artery. [20][21][22] Interestingly, we found that the median size of the implanted PV was larger in the TPVR group (26 mm [21-29]) than in the SPVR group 24 mm [24][25]; P ¼ .002). This was more obvious in patients with native RVOT, where the median implanted PV size in the TPVR group was 29 mm (26-29), compared with Q31 Q30 24 mm in the SPVR group (P < .001).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Surgical implantation of PV in RVOT is a difficult procedure because the oversize prostheses will invariably get compressed anteriorly by the sternum or compromised at the bifurcation of the pulmonary artery. [20][21][22] Interestingly, we found that the median size of the implanted PV was larger in the TPVR group (26 mm [21-29]) than in the SPVR group 24 mm [24][25]; P ¼ .002). This was more obvious in patients with native RVOT, where the median implanted PV size in the TPVR group was 29 mm (26-29), compared with Q31 Q30 24 mm in the SPVR group (P < .001).…”
Section: Discussionmentioning
confidence: 76%
“…However, this was not significant in the immediate postoperative period. QRS duration and cardiac MRI findings are correlated with postoperative patients with TOF, [25][26][27] and these arrhythmias can predict survival. [2][3][4]28 Therefore, we assessed the QRS duration as a surrogate variable for RV dilatation.…”
Section: Discussionmentioning
confidence: 99%
“…QRS duration >170 msec in children is associated with risk of ventricular tachycardias (VT) but as a whole, the QRS duration is significantly shorter in our cohort ( 10 ). The relationship between QRS duration and RV size and function has been questioned with varying results and may be less prolonged with the transatrial approach of primary repair ( 29 31 ). This is consistent with the findings by Lubocka et al, where the correlation with RV function only is seen with patients with early repair ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between QRS duration and RV size and function has been questioned with varying results and may be less prolonged with the transatrial approach of primary repair ( 29 31 ). This is consistent with the findings by Lubocka et al, where the correlation with RV function only is seen with patients with early repair ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…CMR presents all these findings with high accuracy, known as the gold standard but expensive method (8). Furthermore, less diastolic compliance can increase end-diastolic pressure and heart failure (9). Scars at the RV outlet result in conduction delay and arrhythmia in the ventricles (9).…”
Section: Introductionmentioning
confidence: 99%